The lacustrine deposits of Fornaci di Ranica (late Early Pleistocene, Italian Pre-Alps): stratigraphy, palaeoenvironment and geological evolution - C. Ravazzi; R. Pini; M. Breda; E. Martinetto; S. Chiesa; S. Confortini; R. Egli; G. Muttoni (Quaternary International, 2005)
An interdisciplinary investigation of the Pleistocene clay succession of Fornaci di Ranica (Italian Pre-Alps) aimed to reconstruct the palaeoenvironmental history and its chronostratigraphic position and to consider the implications for the Quaternary evolution of the southern alpine borderland near the Early/Middle Pleistocene transition. A detailed survey of Quaternary deposits in boreholes and exposed sections provided a complete record of the basin. The most complete core was analyzed for palynology and magnetic properties. Plant macrofossils were obtained by flotation. Pollen and spectrometric analysis allowed a precise stratigraphic placement of a moose antler and braincase kept in museum collections. The basin originated from fluviatile obstruction of a tributary valley cut into bedrock. The basal deposits formed as a terrestrial hydromorphic soil under a dense Tsuga-forest (zone RNC 1). The overlying palustrine gyttja shows a marked forest withdrawal with a climatic signature (zone RNC 3), followed by a re-establishment of mixed conifer forests (zones RNC 4-6). The occurrences of pollen of cold-adapted taxa (Saxifraga oppositifolia type, Saxifraga stellaris type, Larix), are the oldest so far known south of the Alps and suggest that mean summer temperature was near or even below the thermic tree limit. High herb diversity, partially represented by tall forbs, characterizes this zone. A further increase of the water table can be assumed in zones RNC 4 and RNC 5, since pollen of aquatic plants increases. The find of Larix decidua L. cones demonstrates the existence of the European larch in the Early Pleistocene of the Alps, previously not identified at the species level. After the Serio river had reached the maximum Quaternary aggradation, the lake was rapidly filled up with turbiditic sediments. The identification of Cervalces latifrons (Johnson, 1874) by Azzaroli (Palaeantogr. Italica 71(1979) 48) was confirmed. Pollen spectra obtained from clay fragments preserved in the braincase allowed us to ...